Young girl presenting with exercise‐induced myoglobinuria. Issue 1 (28th April 2016) - Krishnaiah, Balaji; Lee, Jennifer Jheesoo; Wicklund, Matthew Paul; Kaur, Divpreet
ABSTRACT: Introduction : The sarcoglycanopathies are a heterogeneous group of autosomal recessive limb‐girdle muscular dystrophies that cause varying degrees of progressive proximal muscle weakness. Methods : We describe the case of a Caucasian girl who presented with exercise intolerance, myalgia, and dark urine. Onset of symptoms was at age 4, and she had myalgia with physical activity throughout childhood. Creatine kinase levels were as high as 18, 000. Results : Immunostaining of a muscle biopsy showed mildly diminished alpha sarcoglycan staining, and SGCA gene sequencing revealed n.C229T; p.Arg77Cys (R77C) and n.C850T; p.Arg284Cys (R284C), which is associated with alpha sarcoglycanopathy. Conclusions : This patient presented with exercise intolerance, myoglobinuria, and almost normal muscle strength into adolescence, which is uncommon in sarcoglycanopathies. This uncommon presentation should be kept in mind, so that early recognition and intervention may prevent future comorbidities and help preserve the quality of life. Muscle Nerve 54 : 161–164, 2016